Contributions to the study of the subtribe Eremophlepsiina Dmitriev, 2002 (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini) - Tishechkin, Dmitri Yu. (Zootaxa, 2023)
Three species of Eremophlepsiina, Eremophlepsius rohdendorfi, E. sexnotatus, and Pseudophlepsius binotatus are redescribed, variability of their coloration and genitalia is illustrated, the status of some subspecific taxa is discussed. Oscillograms of the male calling signals of E. sexnotatus and P. binotatus are given. The synonymy E. sexnotatus Kusnezov, 1929 = E. parvulus Dlabola, 1961, syn. n. is established.